Istota i projekt rachunku kosztów logistyki w przedsiębiorstwie handlowym - Skoczylas, Krystyna (The Essence and Draft of the Cost Accounting in the Area of Logistics, 2006)
The paper describes the cost accounting in the area of logistics. The classification and the register of costs of logistics are depicted. The advantages with proposed register of costs of logistics were also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 380-388